Pengaruh Financial Target, Financial Stability, dan Ineffective Monitoring terhadap Kecurangan Laporan Keuangan - Oom Tikaromah; Adibah Yahya; Rina Nurjanah; Meli Andriyani; Ida Yanti (Owner : Riset dan Jurnal Akuntansi, 2026)
Fraudulent financial reporting remains a critical issue because it reduces the credibility of financial statements and undermines investors' confidence in the capital market. Based on the Fraud Triangle Theory, financial pressure and opportunity are considered important drivers of financial reporting fraud. This study aims to examine the effects of financial target, financial stability, and ineffective monitoring on fraudulent financial reporting in food and beverage companies listed on the Indonesia Stock Exchange (IDX). The study employs a quantitative approach using panel data collected from 56 listed companies during the 2021–2025 period. Fraudulent financial reporting is measured using the F-Score model. In contrast, financial target is proxied by Return on Assets (ROA), financial stability by asset growth, and ineffective monitoring by the proportion of independent commissioners (BDOUT). Panel data regression analysis was conducted using the Fixed Effect Model (FEM). The findings indicate that financial target and financial stability do not significantly affect fraudulent financial reporting, whereas ineffective monitoring has a positive and significant effect. These results suggest that weaknesses in corporate governance play a more important role than financial pressure in explaining fraudulent financial reporting in Indonesian food and beverage companies. Therefore, strengthening monitoring mechanisms is essential to reduce opportunities for financial statement manipulation. This study contributes by providing updated empirical evidence using the F-Score model in the Indonesian food and beverage sector.